The Effectiveness of Combined Use of Antioxidant and Glutamine in Abdominal Sepsis - V. V. Nazaretyan; V. N. Lukach; A. V. Kulikov (Общая реаниматология)
Aim of the study: the effectiveness of concomitant use of antioxidant therapy with antioxidant 2-ethyl-6- methyl-3-hydroxypyridine succinate (mexidol) and intensive nutritional support with glutamine in patients with abdominal sepsis (AS). Materials and methods. 170 patients with abdominal sepsis (AS) involved in the study were separated into two groups. Patients of group 1 (control group, n=70) received basic treatment. Patients from group 2 (n=100) were divided into 2 subgroups. Patients from the subgroup 21 (n=70), in additon to the basic treatment, received intravenously, by drop infusion, mexidol (2000 mg per day) and dipeptiven (27.5 g per day), patients from subgroup 22 (n=30) additionally to that received per os glutamine. Survival analysis was carried out according to the Kaplan-Meier method with using of the Cox's F-test and Mantel-Cox test for testing of statistical hypotheses. Results. Treatment outcomes analysis showed that in the basic group 2, mortality was lower than in the control group 1. A statistically significant increase of cumulative part in the survivors was revealed using mexidol and glutamine. Conclusion. Concomitant intravenous administration of medications had positive effects on treatment outcomes. Following on from the analysis results, we may suggest that the pair mexidol + dipeptiven interrupts the cascade of development of abdominal sepsis and contributes to avoiding a critical condition during sepsis.